Impact of COVID-19 on the patient visits in ortho emergency at a tertiary care centre - Choudhary, Nitin; Gupta, Akhil; Gupta, Sanjeev; Saharan, Amar (International Journal of Research in Medical Sciences, 2020)
Background: COVID-19 pandemic effects are still being elucidated. Stay-at-home orders issued during peak of COVID-19 and social distancing as lockdown measures compounded with COVID-19 concerns have caused significant disruptions in daily life. One notable effect of these variables may be a change in the number of emergency department (ED) visits. This study aims to investigate the effects of COVID-19 on ED visits, and possible reasons for changes. Methods: Retrospective analysis using data for ED visits and procedures performed in the orthopaedics department of GMC Jammu were collected from the record section of GMC Jammu for four months prior and post implementation of lockdown and results were deduced with regards to the comparison in the number of visits, admissions and surgeries done pre and post-lockdown period. Results: The mean number of ED visits/admissions per day for the last four months of available data post lockdown due to COVID-19 pandemic was significantly less than the four months prior to COVID-19 pandemic. Conclusions: A number of factors have likely contributed to the substantial decrease in ED visits observed in this study. In light of these findings, it is important to raise patient awareness regarding conditions that require urgent ortho consultation so as to avoid any type of deformity/disability whatsoever.